2013
DOI: 10.1097/qai.0b013e318278ba1b
|View full text |Cite
|
Sign up to set email alerts
|

HIV Postexposure Prophylaxis in an Urban Population of Female Sex Workers in Nairobi, Kenya

Abstract: "PEP services were accessed by 10% of FSWs during the study period and were not implicated in any incident HIV cases." Users had indicators of increased sexual risk and higher health care literacy. Increasing PEP access and compliance in FSWs may be an important HIV prevention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
2
23
1
3
Order By: Relevance
“…As expected, heterogeneity was high (τ 2 =492). Excluding two studies that did not report full 28-day adherence yielded a pooled adherence estimate of 82% (95% CI 76 to 88%)(14,21). Assuming that all participants who were lost to follow-up, pooled adherence was 67% (95% CI 59 to 74%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, heterogeneity was high (τ 2 =492). Excluding two studies that did not report full 28-day adherence yielded a pooled adherence estimate of 82% (95% CI 76 to 88%)(14,21). Assuming that all participants who were lost to follow-up, pooled adherence was 67% (95% CI 59 to 74%).…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to ART has been shown to be higher in developing countries compared to developed countries: one meta-analysis found a pooled estimate of adherence to ART in African studies of 77%, compared to an estimate of 55% in North America(43), while another found adherence to PEP after sexual assault was higher adherence in developing (53%) than developed countries (33%)(31). The only study included in our meta-analysis from a generalized epidemic setting included only female sex workers, a high-risk population may not be representative of the general population that may access PEP in Kenya or in other generalized epidemics(21). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential for PrEP and PEP to reduce the acquisition of HIV infection among sex workers, MSM and people who use and inject drugs (Izulla et al 2013; Landovitz et al 2012; Mack et al 2014; McGowan 2014), future research should be conducted to examine the feasibility of these interventions in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…112 Because the probability of HIV transmission via unprotected sex and needle sharing is similar to occupational exposure, post-exposure prophylaxis should be offered to eligible sex workers experiencing an unplanned exposure (sexual or via injected drug use) to an HIV infected person. [113][114][115][116] For exposure to someone of unknown HIV status, the provider and sex worker should jointly decide, based on local HIV prevalence, exposure type, and factors such as trauma and co-existent sexually transmitted infections. 114 Rape survivors should be prioritised for post-exposure prophylaxis because of the likelihood of genital injuries and to help overcome psychological trauma.…”
Section: Hiv Post-exposure Prophylaxismentioning
confidence: 99%